Dialysis Access Management - Wu, Steven; Kalva, Sanjeeva P.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This practical book covers the basic principles and practice of dialysis access management, a crucial part of the care of patients undergoing hemodialysis. It has been written in an easy-to-read, step-by-step format to help facilitate learning and understanding of the procedures, and has been supplemented with numerous operative photographs and diagrams demonstrating the commonly performed dialysis access exams, interventions, procedures and surgeries. Dialysis Access Management is an essential text for residents, fellows, and physicians who are learning or practicing in dialysis and/or dialysis access management, especially in the fields of nephrology, radiology, surgery, and vascular medicine.
Angiographic Imaging Equipment -- Endovascular Tools -- Basic Endovascular Skills and Techniques -- Radiation Safety -- Conscious Sedation and Anesthesia Care -- Vascular Anatomy for Hemodialysis Access -- Hemodialysis Access: Types -- Hemodialysis Access: Physical Examination and Surveillance -- Hemodialysis Access: Imaging Diagnosis -- Angiogram and Angioplasty -- Declotting of Hemodialysis Arteriovenous Access -- Endovascular Stent Placement -- Minimally Invasive Banding Procedure -- Peripheral Arterial Disease in Hemodialysis Access -- Non-tunneled Hemodialysis Catheter -- Tunneled Hemodialysis Catheter -- Surgical Placement of Hemodialysis Vascular Accesses -- Surgical Management of Deep Fistulae Veins -- Preoperative and Postoperative Care for Hemodialysis Vascular Access Surgery.
Keywords: Medicine; Interventional radiology; Nephrology; Vascular surgery; Medicine & Public Health; Nephrology; Interventional Radiology; Vascular Surgery; Electronic books